Hambatan Mahasiswa Kristen Perantauan Untuk Aktif Dalam Persekutuan Pemuda Gereja Di Kota Luwuk - Silanno, Randela G. Billy; Ruindungan, Leo Mardany; Frans, Edison (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
This research wants to answer why many overseas Christian students are not active in church youth fellowships where they are studying. The research was conducted on Christian students at one of the universities in Luwuk city, Banggai district, Central Sulawesi. The method used is quantitative with a survey approach. Data was collected by questionnaire and analyzed by descriptive statistics. Four indicators are used: cultural, communication, economic, and social relationships. The research results show that three of them are barriers that are cultural, economic, and social relationships. For this reason, churches in Luwuk need to develop a service system, especially in youth fellowships, making it easier for overseas Christian students to participate actively.